Calcium imaging revealed no modulatory effect on odor-evoked responses of the Drosophila antennal lobe by two populations of inhibitory local interneurons - Martin F. Strube-Bloss (Nature Portfolio, 2017)
Abstract Although we have considerable knowledge about how odors are represented in the antennal lobe (AL), the insects’ analogue to the olfactory bulb, we still do not fully understand how the different neurons in the AL network contribute to the olfactory code. In Drosophila melanogaster we can selectively manipulate specific neuronal populations to elucidate their function in odor processing. Here we silenced the synaptic transmission of two distinct subpopulations of multiglomerular GABAergic local interneurons (LN1 and LN2) using shibire (shi ts ) and analyzed their impact on odor-induced glomerular activity at the AL input and output level. We verified that the employed shi ts construct effectively blocked synaptic transmission to the AL when expressed in olfactory sensory neurons. Notably, selective silencing of both LN populations did not significantly affect the odor-evoked activity patterns in the AL. Neither the glomerular input nor the glomerular output activity was modulated in comparison to the parental controls. We therefore conclude that these LN subpopulations, which cover one third of the total LN number, are not predominantly involved in odor identity coding per se. As suggested by their broad innervation patterns and contribution to long-term adaptation, they might contribute to AL–computation on a global and longer time scale.